Bibliometric Analysis of Hybrid and Distance Learning Literature in the Digital Age - Mardiani, Eri; Riniati, Wa Ode; Mokodenseho, Sabil; Podomi, Adelia; Mamonto, Jessyka (The Eastasouth Journal of Learning and Educations, 2024)
This bibliometric analysis delves into the literature on hybrid and distance learning within the digital age, examining its evolution, trends, and impact. Through systematic retrieval and analysis of scholarly outputs from 1980 to 2024, key bibliometric metrics, network visualizations, and citation analyses were conducted. The findings reveal a significant transition from traditional to technical research themes over time, reflecting broader societal shifts towards data-driven decision-making. Highly cited works underscore the enduring relevance of foundational concepts and the timely exploration of emergent topics, particularly in response to the COVID-19 pandemic. Moreover, future study directions identified through network visualization offer promising avenues for advancing research agendas in education. This analysis provides valuable insights for educators, policymakers, and researchers, informing evidence-based decision-making and fostering interdisciplinary collaborations in educational innovation.